2002
DOI: 10.1046/j.1469-0691.2002.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural antibiotic susceptibility of Enterobacter amnigenus, Enterobacter cancerogenus, Enterobacter gergoviae and Enterobacter sakazakii strains

Abstract: The present study establishes a database concerning the natural susceptibility of recently established Enterobacter species to a wide range of antibiotics, which can be applied for the validation of routine susceptibility test results. beta-Lactam susceptibility patterns indicate the expression of species-specific beta-lactamases expressed at high or low levels in all the species except E. sakazakii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
52
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 34 publications
4
52
0
1
Order By: Relevance
“…Muytjens & van der Ros-van de Repe (1986) examined Cronobacter susceptibility to 29 antimicrobial agents and found that Cronobacter were the most susceptible among other Enterobacteriaceae studied. This was supported by the finding of Stock & Wiedemann (2002) who showed that Cronobacter were repeatedly susceptible to b-lactams with no evidence for the expression of b-lactamase. In contrast, Pitout et al (1997) demonstrated that some strains of Cronobacter produce b-lactamase at low levels.…”
Section: Antibiotic Susceptibility and Resistancementioning
confidence: 71%
“…Muytjens & van der Ros-van de Repe (1986) examined Cronobacter susceptibility to 29 antimicrobial agents and found that Cronobacter were the most susceptible among other Enterobacteriaceae studied. This was supported by the finding of Stock & Wiedemann (2002) who showed that Cronobacter were repeatedly susceptible to b-lactams with no evidence for the expression of b-lactamase. In contrast, Pitout et al (1997) demonstrated that some strains of Cronobacter produce b-lactamase at low levels.…”
Section: Antibiotic Susceptibility and Resistancementioning
confidence: 71%
“…Originally C. sakazakii has been reported to be susceptible to a wide range of antibiotics including b-lactams, 23 however, several new strains have been described that were found to be resistant to tetracycline, 24 neomycin and trimethoprim 25 and cephalotin. 26 Furthermore, recent studies have described a strain carrying an unusual ampC gene, conferring resistance to cephalosporine 27 and found environmental isolates of C. sakazakii from domestic kitchens exhibiting resistance to penicillin, tetracycline, ciprofloxacin and nalidixic acid.…”
Section: Antibiotic Resistance and Alternative Means Of Controlmentioning
confidence: 99%
“…The lethality of Cronobacter infections is very high (40-80%) and the incidence is relatively low (8.7 per 100 000 low birth weight neonates) [3,4]; however, it is assumed that the number of infections caused by Cronobacter is underreported. Antibiotic therapy is effective if applied soon after infection, but resistance against some therapeutics has already been reported [5]. It can be expected that alternative approaches will be needed soon, since the antimicrobial resistance is rising [6].…”
Section: Introductionmentioning
confidence: 99%